(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted on “Lohman Meat” broiler chicks to evaluate the effect of exogenous multivitamin and enzyme supplementation on body weight gain, haematological parameters (TEC, Hb content, PCV and ESR) and serum transaminases (AST and ALT). A total of 20, twenty days old broilers were randomly divided into four equal groups (5×4). Group A was considered as control, fed only with commercial ration, group B was treated at a dose rate of 0.5 ml multivitamins per 1 litre of drinking water, group C was treated at a dose rate of 1 ml enzyme per litre of drinking water and group D was treated with multivitamin @ 0.5 ml/L and Enzyme @ 1ml/ L in water from 1 to 21 days of experiment. It was observed that multivitamin and enzyme supplementation significantly (p<0.01) increased body weight. TEC, PCV and Hb content increased significantly (p<0.01) in the treated groups as compared to that of control group. ESR, AST and ALT values decreased significantly (p<0.01) in the treated groups. Therefore, it may be concluded that multivitamin and enzyme may be used with better performances in terms of increase of body weight and blood profiles. Keywords: Multivitamins and enzymes; Effects; Broiler DOI: 10.3329/jbau.v8i1.6396 J. Bangladesh Agril. Univ. 8(1): 39-44, 2010